(untitled) (Andamios, Revista de Investigación Social, 2014)
In this study, frequencies and geographic and temporal dispersions of queries made, between August 2012 and September 2013, to the online Dictionary of Mexican Spanish are examined. They are used to compute an index that allows selection of those queries that are most common in more places and during the longest time span. On the one hand, the statistical basis that led to this dictionary’s current nomenclature can be evaluated by means of this index. On the other hand, unanswered queries with highest index values can be considered candidates for future nomenclatures.